(untitled) (Revista Linhas, 2007)
Este estudo, em desenvolvimento, tem como objeto as imagens estéticas e sua significação. Como somos seduzidos pelas imagens do cotidiano? E por quê? Quais são as relações entre a arte e os objetos estéticos? Como alcançar o significado no complexo sistema de significação do texto visual? Palavras-chave: Semiótica visual. Moda. Design industrial. Publicidade. This article has the aesthetic images and gadgets, including the artistics, and their significations, as subject. How are we seduced by aesthetic images and gadgets? And why? There are relationships between artistics images and the aesthetic ones? How can we do to read the texts’ complexity of the visual universe? Key words: Image visual semiotics. Fashion. Design. Product design. Publicity.